2022
DOI: 10.1073/pnas.2117576119
|View full text |Cite
|
Sign up to set email alerts
|

SNX27 suppresses SARS-CoV-2 infection by inhibiting viral lysosome/late endosome entry

Abstract: After binding to its cell surface receptor angiotensin converting enzyme 2 (ACE2), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enters the host cell through directly fusing with plasma membrane (cell surface pathway) or undergoing endocytosis traveling to lysosome/late endosome for membrane fusion (endocytic pathway). However, the endocytic entry regulation by host cell remains elusive. Recent studies show ACE2 possesses a type I PDZ binding motif (PBM) through which it could interact with a PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 68 publications
2
22
0
Order By: Relevance
“…Consistent with our study, recent studies found that ACE2 surface localization was mediated by SNX27 and SARS-CoV-2 S associated with SNX27 ( 5 , 6 , 7 , 8 ). However, those studies did not explore the role for SARS-CoV-2 S in the endocytic recycling of ACE2.…”
Section: Dear Editorsupporting
confidence: 93%
“…Consistent with our study, recent studies found that ACE2 surface localization was mediated by SNX27 and SARS-CoV-2 S associated with SNX27 ( 5 , 6 , 7 , 8 ). However, those studies did not explore the role for SARS-CoV-2 S in the endocytic recycling of ACE2.…”
Section: Dear Editorsupporting
confidence: 93%
“…Thus, a disruption of the scaffolding complexes that anchor ACE2 to the plasma membrane could facilitate endocytosis and virus entry. In agreement with this idea, it was recently reported that ACE2 interacts directly with the cytoplasmic PDZ proteins NHERF1 and SNX27, and these interactions modulate ACE2-mediated SARS-CoV-2 cell entry [ 82 , 83 ]. Interestingly, both NHERF1 and SNX27 also modulate TJ organization and barrier function, by associating with the TJ protein ZO-2 (SNX27) and regulating cytoskeletal organization and membrane trafficking [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, additional pathogens hijack ESCPE-1 cargo recognition to promote intracellular survival (2,3,44), and SNX5 has also recently been identified as a key regulator of innate cellular immunity against a range of viruses (45). Genomewide CRISPR screens and biochemical studies have identified multiple endosomal sorting machineries that facilitate SARS-CoV-2 infection, including components of the retromer, retriever and COMMD/CCDC22/CCDC93 (CCC) complexes (46)(47)(48)(49)(50)(51). Here, we suggest that ESCPE-1 sequence-dependent cargo sorting also plays a role in regulating the endosomal dynamics exploited during SARS-CoV-2 infection, potentially expanding the scope of pathogens that can exploit this complex.…”
Section: Discussionmentioning
confidence: 99%